Watermarking QR Code Application On Birth Certificates Using The Discrete Cosine Transform (DCT) Method - Aulia Firliansyah; Achmad Fauzi; Hermansyah Sembiring (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
The current era's development directs us to understand data security better. Vital documents such as family cards often become subjects of forgery. Therefore, we must be capable of safeguarding the confidentiality of our data. This issue can be addressed through watermarking methods. Watermarking is a technique that can be used to embed information into an image. A digital image represents a machine-captured approximation of an image based on sampling and quantization. The image utilized here employs QR Code, which represents the evolution of one-dimensional barcodes into two-dimensional forms. This study employs the Discrete Cosine Transform (DCT) algorithm. This algorithm converts data from spatial form by segmenting images into sub-parts with varying frequencies. The application of the Discrete Cosine Transform (DCT) method in watermarking the QR Code on birth certificates has significantly contributed to the security and authentication of the document. Throughout this implementation, DCT has proven to be an effective tool for embedding additional information into birth certificate images without compromising the integrity of the main information. However, it should be noted that the use of DCT can also impact the visual quality of the image. Thus, parameter adjustments are necessary to strike the right balance between security and visual aesthetics.